2006
DOI: 10.1080/15389580500482021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Biomechanical Response of Kidneys Under Blunt Impact

Abstract: The kidneys showed a viscoelastic response. An energy-based injury threshold was identified, with a strain energy density of 21 kJ/m(3) corresponding to a 50-percent risk of renal injury level AIS3 or higher. Finally, the impact tests were simulated using a finite element model of the kidney to investigate relevant injury mechanisms. The model predicted the renal capsule and underlying parenchyma to first fail at an impact energy level of 4.0 J, consistent with experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
3
2
2
Order By: Relevance
“…The studies found in the literature reported a threshold value for injuries with an AIS 3 of 4 J [11,[13][14][15] and for a first sign of kidney injury at 1.4 or 2.7 J [11,12], which are at least 5 times lower than the values determined in this study (see Fig. 4 and 5).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The studies found in the literature reported a threshold value for injuries with an AIS 3 of 4 J [11,[13][14][15] and for a first sign of kidney injury at 1.4 or 2.7 J [11,12], which are at least 5 times lower than the values determined in this study (see Fig. 4 and 5).…”
Section: Discussioncontrasting
confidence: 72%
“…The gelatin block shows the chosen mesh with the SED distribution. Enlarged: Section showing the interface between the impactor and the gelatin with the gelatin sticking to the impactor (red arrow) values related to an organ injury determined in this study are much higher than values found in the literature [11][12][13][14][15][16] has three reasons: (i) the literature data were obtained by slowly squeezing tissue samples or the whole organ between two hard plates which hindered the organ to bend as expected in a realistic situation of blunt impact; (ii) the literature data represent mean values over a large sample volume or even the whole organ whereas our data display the SED inside one single voxel; (iii) in this study the organs were surrounded by gelatin, which has a protecting effect on the organ.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Soft tissues typically behave as hyper-elastic/hyperviscoelastic nearly incompressible continuum and the parameters for such models have been determined only for a limited number of the abdominal/thoracic organs (Miller 2000;Leroy et al 2001;Schmitt and Snedeker 2006;Gao et al 2010;Shao et al 2013). Therefore, a hyper-elastic (Mooney -Rivlin) constitutive model was used for the liver and kidney and a linear viscoelastic constitutive model for the remaining tissues, organs, muscles and ligaments (Lizee et al 1998;Robin 2001;Ruan et al 2003;Kimpara et al 2005;Ruan et al 2005) (Table 8).…”
Section: Mesh Loading Boundary Conditions and Materials Properties Fmentioning
confidence: 99%